FORMATION OF THE STUDENT’S ECOLOGICAL CULTURE THROUGH VOLUNTEER ACTIVITY - Angela I. Abdurazakova; Lukman S. Aygubov; Kurban I. Khadzhialiev (Юг России: экология, развитие)
Abstract. The aim of the research is to study some aspects of the effective formation and development of the ecological culture of the students in the republic of Dagestan as well as to analyze the influence of the pedagogical potential of social volunteering on the formation of the socio-ecological culture of youth. Discussion. Many current socio-ecological problems, specific to Dagestan and many other regions of Russia, are of great interest and concern to modern youth. Student youth (aged 14-25 years) in Dagestan make up about 28% of the total population of the republic. Purposeful and systematic work with young people in order to form the right socio-ecological views and ideas, develop self-motivation and readiness to engage in specific environmental activities for the benefit of the society seems to us an extremely important direction of the educational process. Environmentally oriented volunteer activity of young people has a high potential for solving the problems indicated in the study. Conclusion. In recent years, the Republic of Dagestan has seen a steady growth in the number of young citizens and organizations involved in volunteerism, thus the scope of volunteer programs and projects is expanding. And one of the most important and effective areas, both in terms of the number of events and  the scope and involvement of young people, is the environmentally oriented volunteer activity of young people.